2020
DOI: 10.1002/brb3.1837
|View full text |Cite
|
Sign up to set email alerts
|

Mental health and quality of life among healthcare professionals during the COVID‐19 pandemic in India

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
166
7
10

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 212 publications
(245 citation statements)
references
References 26 publications
12
166
7
10
Order By: Relevance
“…Regarding the age of HCPs, this study reported similar results to those found in Jordan and other countries, where young HCPs were more psychologically affected than others [ 12 , 47 , 48 , 49 , 54 ]. This could be attributed to the fact that young HCPs may have less experience or they may have such fear because they might be parents of children, and young people who need more attention and effort in improving their knowledge about the preventive measures.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Regarding the age of HCPs, this study reported similar results to those found in Jordan and other countries, where young HCPs were more psychologically affected than others [ 12 , 47 , 48 , 49 , 54 ]. This could be attributed to the fact that young HCPs may have less experience or they may have such fear because they might be parents of children, and young people who need more attention and effort in improving their knowledge about the preventive measures.…”
Section: Discussionsupporting
confidence: 85%
“…Although the current findings showed slight differences in depression and anxiety rates, doctors reported lower levels of mental distress compared to other HCPs. However, results reported from India were in opposition those of all of the previous studies, and showed no differences between doctors and nurses in their mental distress level during the pandemic [ 48 ].…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Also, people with chronic mental disorders may have been disproportionately affected during this pandemic who may have lost access to care and other services. Moreover, coexisting mental disorders among the same individuals may affect the overall health and quality of living 71,79,92,93 . Future research should pay special attentions to investigate anxiety, depression, and other mental health problems among those vulnerable individuals and populations.…”
Section: Sensitivity Analysis and Publication Biasmentioning
confidence: 99%
“…Pooled prevalence of anxietyA total of 31 studies reported the prevalence of anxiety during COVID-19 in different samples from South Asian countries[46][47][48][49][50][51][52][53][54][55][56]58,59,[61][62][63][64][65][66]68,69,[71][72][73][74][75][76][77][78][79][80] . These studies used different scales to measureanxiety in respective samples, including the Generalized Anxiety Disorder 7-item (GAD-7) scale (n = 16), Depression, Anxiety and Stress Scale -21 Items (DASS-21) scales (n = 9), Hospital Anxiety and Depression Scale (HADS) (n = 4), Patient Health Questionnaire-4 (PHQ-4) (n = 1), and Self Reporting Questionnaire 20-items (SRQ-20) scale (n = 1).…”
mentioning
confidence: 99%